Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Mewarnai Dengan Teknik Usap Abur - Mujiwati Mujiwati; Rizki Amalia; Joni Joni (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The background of this research is the low fine motor skills in group B children at Nurul Hikmah Kindergarten. One solution to this problem is to apply coloring activities using the smear technique. This study aims to find out whether coloring activities using the smear technique can improve fine motor skills in group B at Nurul Hikmah Kindergarten. The subjects in this study consisted of 11 children, 8 girls and 3 boys. The method used in this research is Classroom Action Research (CAR). This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings. Data collection techniques used observation and documentation. The results showed that there was an increase in the development of fine motor skills in each child indicator with BB criteria (Not yet Developed) experienced a reduction in children from pre-cycle there was 72.7% in cycle I there was 27% and cycle II there were no more children with criteria Undeveloped. The MB criteria (Beginning to Develop) from 18.2% in the pre-cycle increased in cycle I to 52.75% and in cycle II there were no children with the Starting to Develop criteria. BSH criteria (Developing According to Expectations) increased from 9.1% to 20.72% in cycle I and cycle II increased again to 38.25%. BSB criteria (Very Well Developed) in the initial conditions and cycle I there were no children who developed very well but in cycle II it increased to 61.75%. Keywords: Fine Motor Skills, Varied Swab Technique, Classroom Action Research